Postmodernism and the environmental crisis - Gare, Arran, 1948- (Routledge, 1995)
Gare has produced one of the first books to combine cultural theory and environmental philosophy. He critiques the current philosophies of the environmental movement and suggests his own controversial theory of a new postmodern worldview.